The Trial by Social Media Phenomenon: Its Implications on Judges' Conviction and the Protection of Judicial Independence - Irwansyah Tanjung; Chairus Suriyati (CERED Indonesia Institute, 2025)
The influence of social media pressure on the process of forming a judge's conviction within the Indonesian criminal justice system corresponds with the advancement of digital technology, which has shifted the pattern of public oversight from trial by the press to trial by social media, thereby shaping a court of public opinion. Sociological phenomena such as the “No Viral, No Justice” movement and justice outsourcing generate psychological pressure that potentially encourages the practice of judicial populism. Consequently, the independence of the judicial power and the cognitive independence of judges in evaluating evidence pursuant to Articles 183 and 184 of the Criminal Procedure Code (KUHAP) face tangible external challenges. Utilizing a normative legal research method with approaches in the sociology of law, legal realism, statutory examination, conceptual analysis, and case studies, this research formulates solutions for institutional protection. The findings indicate the necessity of reactualizing the contempt of court doctrine and the sub judice rule, supported by Article 281 of Law Number 1 of 2023 concerning the Penal Code. Furthermore, the panel of judges may optimize its functional authority through procedural discretion, consisting of restricting live broadcasting (live streaming) and applying publication restriction orders (gag orders) to ensure a fair trial. The discovery of material truth must remain grounded in trial facts, rather than digital trends.